USING MODELS TO DEAL WITH HAZARDS AND DISASTERS: A TRAJECTORY TOWARDS EFFECTIVE DISASTER MANAGEMENT IN ZIMBABWE - Dube, Ernest (PEOPLE: International Journal of Social Sciences, 2018)
The contribution of models in the management of disasters has been less understood by some practitioners. As such, the use of models seems to have been ignored by policy-makers and practitioners when dealing with all forms of disasters in Zimbabwe. Various kinds of hazards and disasters in Zimbabwe, that include droughts, floods, cholera epidemics and veld fires have heavily impacted communities, resulting in the complexity of disaster management that calls for the use of models. This desktop study sought to analyze the contribution of models in managing hazards and disasters in Zimbabwe. The study was based on a qualitative literature survey and document analysis. Through literature and document analysis, the study found that models are crucial in disaster management as they can simplify practitioners’ understanding of hazards and disasters. Models are also a useful and indispensable decision-making support tool as they can assist the practitioners to make appropriate decisions. The study further found that models that are common to the practitioners included the traditional model, expand-contract model, and the disaster crunch model. Furthermore, a close relationship exists between the disaster management models. Most of the models are based on the disaster management phases of mitigation, preparedness, response and recovery. Since the models play a significant role in the management of hazards and disasters, the study concluded that they are an indispensable tool and a proper trajectory towards managing disaster events in Zimbabwe. Therefore, the study recommends the adoption of the models in the management of all forms of disasters. The significance of this study is in its potential to inform policy and practice. The future scope should focus on the nature of models applicable to selected disaster situations in Zimbabwe.